Trends in Land-Use and Land-Cover Change: Key Insights for Managing the Atlantic Forest Transition - Carvalho Costa, Henrique Simões (2024)
Studies on land-use and land-cover change patterns contribute to better informed management decisions for the conservation and restoration of Atlantic Forest fragments and their megabiodiversity. In recent decades, the phenomenon of forest transition has been observed in several parts of the biome, including in highly urbanized and metropolitan areas such as Campinas, in the state of São Paulo. Here, we examine land-use and land-cover change (using MapBiomas data with 30 m spatial resolution) within the Campinas Environmental Protection Area, where natural forest cover increased from 9% to 17.1% of the total area between 1985 and 2023. Exogenous socioeconomic factors, including the gradual replacement of agricultural activities by tourism development and the designation of areas through successive ecological–economic zonings, are presented as possible causes of the decrease in deforestation and the stabilization and recovery of the remaining natural forest cover. Our analysis reaffirms evidence from other studies showing that secondary succession in abandoned pastures contributed to the forest transition process identified in the region. Strongly decreasing trends were identified for pasture areas and strongly increasing trends for forest formations and urban infrastructure. Based on analysis of forest formation transitions conducted at 5-year intervals between 1985 and 2020, we observed different patterns of net change between the local, regional, and macroregional levels and the state and biome levels. Our analysis of land-use and land-cover transitions for the most recent years (2018 to 2023), including the period of validity of the EPA Management Plan, indicates that the ecological–economic zoning instrument is effective in containing potential threats; however, it has limitations, since losses of forest formation were observed in all five conservation zones. We emphasize that, although we can attest to the effectiveness of ecological–economic zoning, which in the EPA region has undergone incremental adaptations favorable to the forest transition process, this management instrument is subject to changes in its limits and regulations based on the governance system established at its different levels.